The role of Great Barrier Reef tourism operators in addressing climate change through strategic communication and direct action. Issue 2 (1st February 2018) - Goldberg, Jeremy; Birtles, Alastair; Marshall, Nadine; Curnock, Matt; Case, Peter; Beeden, Roger
ABSTRACT: The projected decline in reef health worldwide will have huge repercussions on millions of stakeholders depending upon coral reefs. Urgent action is needed to sustain coral reefs into the future. Tourism operators are recognised as stewards of Australia's Great Barrier Reef (GBR), a World Heritage Site, and are taking action on climate change, through their business practices and by engaging guests with interpretation and targeted messages. Yet little is known about how tourism operators along the GBR perceive climate change, or what actions they believe are most effective to address climate change impacts on the GBR. We describe a set of semi-structured interviews with 19 tourism operators in the Whitsundays and Cairns, the most popular tourism destinations along the GBR. Using a thematic analysis to code and report patterns within the data, we show tourism operators recognise the threat of climate change and strongly support increased action to address it. Most respondents are hesitant to engage their guests about climate change despite acknowledging an interest, expertise, and responsibility to do so. Understanding the barriers preventing tourism operators from addressing climate change is an important step towards helping them, and the tourists visiting the region, take action to protect the GBR.